2014
DOI: 10.1186/bf03352376
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of GPS/MET retrieved ionospheric electron density and ground based ionosonde data

Abstract: The Global Positioning System/Meteorology (GPS/MET) mission has been the first experiment to use a low Earth orbiting (LEO) satellite (the MicroLab-1) to receive multi-channel Global Positioning System (GPS) carrier phase signals and demonstrate active limb sounding of the Earth's atmosphere and ionosphere by radio occultation technique. Under the assumption of spherical symmetry at the locality of the occultation, the dual-band phase data have been processed to yield ray-path bending angle profiles, which hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 26 publications
3
60
1
Order By: Relevance
“…Hajj & Romans (1998) considered, for instance, the GPS single-frequency signal bending in the ionosphere and used the Abel inversion to derive EDPs to perform a validation between GPS/MET profiles with ionosonde measurements during low solar cycle conditions with a bending angle <0.01°. It was concluded that the accuracy of NmF2 yields around 20% of its absolute level, which was later confirmed by Tsai et al (2001). Furthermore, to estimate the absolute precision of the classical Abel inversion, Schreiner et al (2007) studied the accuracy of N e by co-located F-3/C EDPs and obtained a root-mean-square (RMS) difference of approximately 10 9 el/m 3 , a value which indicates already, that rough discrepancies cannot be ruled out by using the classical approach.…”
Section: Introductionmentioning
confidence: 62%
“…Hajj & Romans (1998) considered, for instance, the GPS single-frequency signal bending in the ionosphere and used the Abel inversion to derive EDPs to perform a validation between GPS/MET profiles with ionosonde measurements during low solar cycle conditions with a bending angle <0.01°. It was concluded that the accuracy of NmF2 yields around 20% of its absolute level, which was later confirmed by Tsai et al (2001). Furthermore, to estimate the absolute precision of the classical Abel inversion, Schreiner et al (2007) studied the accuracy of N e by co-located F-3/C EDPs and obtained a root-mean-square (RMS) difference of approximately 10 9 el/m 3 , a value which indicates already, that rough discrepancies cannot be ruled out by using the classical approach.…”
Section: Introductionmentioning
confidence: 62%
“…Derivation of the ionospheric electron density from RO measurements is described in more detail by Tsai et al (2001). At CDAAC, the ionospheric profiles are also retrieved by the Abel inversion from TEC along LEO-GPS rays.…”
Section: Cosmic Datamentioning
confidence: 99%
“…Nevertheless [e.g., Tsai et al, 2001], retrieved profiles from RO data frequently depict negative or positive bias or even negative N e values below altitudes around 100 km. These errors are due to (1) the considerable spatial extension of the averaging in the retrieval process around the tangent point at ionospheric heights (≈ 1000 km) and (2) the spherical inhomogeneity of N e , expected at low and midlatitude regions (in the lower neutral atmosphere the averaging around the tangent point in the T retrieval process is considerably lower).…”
Section: Wave Activity In the Ionosphere Above The Andesmentioning
confidence: 99%